2020
DOI: 10.18196/ijief.2120
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Economic Evaluation of Zakah-Poverty Nexus in Kano State, Nigeria

Abstract: Nigeria is the largest economy in Africa and yet, a poverty-ridden oil-producing country. Thus, poverty remains a persistent macroeconomic challenge in Nigeria with devastating consequences, especially in the Muslim populated states like Kano. Surprisingly, Kano state, which is the most populated state in Nigeria with more than 15 million people, is one of the 14 most poverty-ridden states in Nigeria, despite the practice of Zakah institution (ZI). Therefore, this study empirically evaluates the revenue base a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 5 publications
(12 reference statements)
0
20
0
4
Order By: Relevance
“…Fortunately, some of them were previous beneficiaries of the zakat. Similarly, Mustafa (2020) found that 707 zakat payers, who represented 78.6% of the respondents, were found to fall into the class of high ability zakat payers between 5,000-₦1 m and above. They believed this is a clear indication of a high level of the potential revenue base of the zakat institution in Kano state.…”
Section: Discussion Of Findingsmentioning
confidence: 95%
See 3 more Smart Citations
“…Fortunately, some of them were previous beneficiaries of the zakat. Similarly, Mustafa (2020) found that 707 zakat payers, who represented 78.6% of the respondents, were found to fall into the class of high ability zakat payers between 5,000-₦1 m and above. They believed this is a clear indication of a high level of the potential revenue base of the zakat institution in Kano state.…”
Section: Discussion Of Findingsmentioning
confidence: 95%
“…Earlier mentioned in Islamic accounting, inventories are measured at their market values for the purpose of zakat with a view to maximizing zakat revenue for the socioeconomic development of the Ummah (Abdul Rahman and Awang 2003, p. 34;Abdul Rahman 2007, p. 97;Awang and Mokhtar 2012, p. 289). In specific, Mustafa et al (2020) established that lack of proper recordkeeping of zakat revenue by the Kano State Zakat and Hubsi Commission is among the major problems of zakat institution in the state. This contributes significantly to low zakat collections.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zakat in the perspective of social interests is managed in two ways, namely consumptive and productive [7], [8]. Management in productive activities aims to improve the welfare and economic independence of the people [9], [10]. Zakat is one of the characteristics of the Islamic economic system which contains the principle of justice [11], [12], namely the transfer of income from muzakki to mustahik [13], [14].…”
Section: Introductionmentioning
confidence: 99%